A qualitative examination of substance use disorder treatment-seeking among women with opioid use disorders: The role of syndemics and structural violence - Antoinette L. Spector; Katherine G. Quinn; Staci A. Young; Mallory O'Brien; Terri A. deRoon-Cassini; Julia Dickson-Gomez (Elsevier, 2021)
Women with opioid use disorders (WWOUD) experience disparities in access to substance use disorder (SUD) treatment, yet the reasons for these differences are unclear. Co-occurring social and structural factors may work synergistically to impede women's treatment-seeking efforts. The current study explored the socio-structural context of SUD treatment-seeking among WWOUD. We used in-depth, semi-structured interviews with 56 women who had misused any opioid in the past year to address the study's aims. Constructivist grounded theory principles were used to identify the socio-structural barriers to SUD treatment entry through the lens of syndemics and structural violence. Study results illustrate how WWOUD can encounter a host of mutually reinforcing negative conditions that are situated within the broader socio-structural context of social stigma, poverty, limited availability of SUD treatment options, and a punitive societal approach to drug use. Findings indicate a need to implement and expand structural interventions that address economic and housing insecurity and childcare needs. Strategies that move systems away from a punitive approach to drug use are also encouraged, in favor of supportive and cross-system collaborative approaches that can facilitate women's access to SUD treatment services.